Substituição do cloreto de colina por uma fonte vegetal de colina em dietas de frangos - Dias, Allan Gabriel Ferreira (2021)
The aim of this study was to assess a vegetal source of choline as a replacement of choline chloride and its effects in the animal performance, metabolism and yield of broilers’ carcass. 1120 one day old male Cobb were used, distributed in four treatments with eight repetitions of 35 birds per unit. The treatments were: 1 - control (choline in the form of choline chloride 60%), 2 – 75% of choline chloride and 25% of vegetal choline (Choline-H) as a source of choline, 3 – 50% of choline chloride and 50% of vegetal choline (Choline-H) as a source of choline, and 4 – 100% of vegetal choline (Choline-H) as a source of choline. The animals’ performance was evaluated (weight gain, feed consumption, feed conversion, viability and uniformity), carcass and cuts yield, feathering patterns, serum biochemical profile, liver and locomotor system health, chest muscular anomalies, and zones of growth of the proximal epiphysis of the broilers’ tibias. There were no significant differences in the evaluation of broilers’ performance (weight gain, feed consumption, feed conversion, and viability) in none of the assessed phases (7, 21, 35 and 42 days). The treatment with 100% of vegetal choline provided greater uniformity of the broilers after 35 days to the carcass yield and the percentage of organs also showed no statistical differences. In the feathering score analysis, no difference was found. However, in the percentage of feathers, the treatment combining the two sources of choline had higher percentage of feathers. For the histopathological analysis and the evaluation of locomotor problems, there were no significant differences between treatments. In the serum biochemical analysis, the treatment using only vegetal choline lowered the levels of LDL and cholesterol in 21 days and of LDL in 42 days, not showing any other significant differences to the other assessed parameters (AF, GGT and AST enzymes, triglycerides, HDL and VLDL). It was concluded that the vegetal source of choline can replace choline chloride as a whole in the diet of broilers, without loss of performance and lowering the levels of circulating LDL.